Understanding the daily work of the nurse-leader - Kauhana Oliveira Kian; Laura Misue Matsuda; Maria Angélica Pagliarini Waidmann (Rev Rene)
This is a qualitative study, of Thematic Analysis which aimed to learn about the nurse leaders’ perception from an institution of public education about their work. The data collection was performed by recorded interviews, with five nurses, throughout the month of November 2009. After organizing and analyzing the data, thematic categories emerged, such as: intervene positively in the performance of the nurse leader; factors that intervene negatively and; influence of leadership style in personal and professional nurse leader’s life. Among other factors that were made salient they included in the first category, the team’s inexperience and exhausting work; in the second category: good working conditions, good pay and personal characteristics of nurses. As for the third category it was included: interference or not of their position in life quality. It was so concluded that in the institution investigated, in general, the nurse leader perceives his work as a possibility of development and professional growth.